PROCEEDINGS OF the 29th Quadrennial Session of the CIE 2019
DOI: 10.25039/x46.2019.op31
|View full text |Cite
|
Sign up to set email alerts
|

Approach to Analyse Seasonal and Geographical Variations in Daylight Illuminants

Abstract: Based on 622 spectral measurements, a reconstruction approach for spectral power distributions of daylight was proposed in 1964. This procedure allows to derive the spectral power distribution of daylight illuminants from their chromaticity coordinates or correlated colour temperature. It suggests that inexpensive sensors can be used to measure daylight and a representation of colour characteristics of daylight can be done with just one single value, without large errors. The reconstruction approach was adopte… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

2
2
0

Year Published

2021
2021
2022
2022

Publication Types

Select...
4

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(4 citation statements)
references
References 19 publications
2
2
0
Order By: Relevance
“…Peyvandi et al [26] calculated the 25% and 75% interquartile values of the CCT to find the range containing 50% of the CCTs for each condition, obtaining a range for clear sky without aerosol particles of 5889-6294 K, a range for clear sky with aerosol particles of 5712-6325 K, and a range for overcast sky of 6218-7757 K. The overcast sky and atmosphere with aerosol particles represented extreme conditions where the limits of the CCT were observed. Daylight measured in Granada (Spain), with the most observed CCTs of 5555-5715 K [24], and in Boulder, Colorado (United States), with obtained CCTs of 5500-6400 K, showed that lower CCTs represented atmospheres with higher aerosol particle levels [23,24]. Similar results were found in Rochester, New York (United States), where daylight with CCT as low as 3530 K in a hazy sky was reported [27].…”
Section: Sky Characteristics and Photopic Descriptionssupporting
confidence: 69%
See 2 more Smart Citations
“…Peyvandi et al [26] calculated the 25% and 75% interquartile values of the CCT to find the range containing 50% of the CCTs for each condition, obtaining a range for clear sky without aerosol particles of 5889-6294 K, a range for clear sky with aerosol particles of 5712-6325 K, and a range for overcast sky of 6218-7757 K. The overcast sky and atmosphere with aerosol particles represented extreme conditions where the limits of the CCT were observed. Daylight measured in Granada (Spain), with the most observed CCTs of 5555-5715 K [24], and in Boulder, Colorado (United States), with obtained CCTs of 5500-6400 K, showed that lower CCTs represented atmospheres with higher aerosol particle levels [23,24]. Similar results were found in Rochester, New York (United States), where daylight with CCT as low as 3530 K in a hazy sky was reported [27].…”
Section: Sky Characteristics and Photopic Descriptionssupporting
confidence: 69%
“…Conversely, in the opposite locations (north and west), the CCTs are altitude-dependent; and the higher the CCT is, the cooler the results that are found. The measured CCTs show variations as a function of the season, orientation and altitude in correspondence with CIE D illuminances, even with clear sky conditions [22,23]. When the value of the sky is considered, daylight approaches 6500 K. The average value of the data taken in this study is 6122 K, similar to the dominant CCT of the study conducted in the city of Granada, Spain (5700 K).…”
Section: Sky Characteristics and Photopic Descriptionssupporting
confidence: 65%
See 1 more Smart Citation
“…The X, Y, Z values obtained from the LumiCam ® were adjusted to the levels of illumination at the time of the measurement through the white reference from the X-Rite ColorChecker ® panel. In addition, the reference illuminant (D100 CIE) has spectral characteristics very similar to the indirect natural light [29].…”
Section: Colorimetric Changes Of the Mosaicmentioning
confidence: 99%